دور جدید میں مسلم مہاجرین کی آباد کاری (سیرۃ النبی ﷺکی روشنی میں): Modern age colonization of Muslim immigrants in the light of Sirat۔al۔Nabi (SAW) - Ghulam Yousaf, (Seerat Studies, 2023)
The problem of Muslim refugee in the world a live challenge for modern world, because its have some causes thought of domination of Jews and rolling all over the world. Secondly over lights past and rolling on 3 continents Asia, Europe and Africa on the base of equality without help of non-Muslim. Non-Muslim dislike that things. Now they make planning to control the Muslim world and show that the defend Jihad a terrorism. In this way according to Jews and Hindus every Muslim is a tsarist because he is acting Jihad religiously and spread terrorism in land. Attack the Jew on Muslim country also a cause of creates problems for Muslim people to migration for other country to safety. In Islamic history when the Holy prophet (SAW) establish the first Islamic state at Medina, issues of immigrants were common that time, but he settled them with great planning .As a result it is a practically role model for mankind specially for Muslim country in modern age because Islam provides us a complete code of life and guide safety and welfare human in emergency and normal position without difference between Muslam and Non-Muslim.